2019
DOI: 10.1016/j.jappgeo.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

New method for denoising borehole transient electromagnetic data with discrete wavelet transform

Abstract: Discrete wavelet transform (DWT) has been widely used as a useful tool in denoising geophysical data for its outstanding feature of detecting singularities and transients. In this paper, we develop a new strategy of denoising borehole transient electromagnetic (BHTEM) data. The principle idea of the denoising process is keeping those coefficients which are necessary to reconstruct the signal unchanged and setting others to zero. In our case, according to results of modeling, only the first eight detail coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This mechanism effectively reduces noise in the image and preserves spectral information. SOC changes are non-stationary and non-linear, and wavelet and Fourier transformations have clear advantages in processing non-stationary data [41,42]. Consistent with our research, Meng et al also demonstrated that DWT is an effective method for reducing noise in hyperspectral images [20].…”
Section: Advantages Of Image Denoising In Satellite Hyperspectral Pre...supporting
confidence: 88%
“…This mechanism effectively reduces noise in the image and preserves spectral information. SOC changes are non-stationary and non-linear, and wavelet and Fourier transformations have clear advantages in processing non-stationary data [41,42]. Consistent with our research, Meng et al also demonstrated that DWT is an effective method for reducing noise in hyperspectral images [20].…”
Section: Advantages Of Image Denoising In Satellite Hyperspectral Pre...supporting
confidence: 88%
“…FT uses large waves, while DWT uses small waves [71]. Similar to FT's transformation, which of time domain signals into triangle functions, DWT decomposes signals into different scale components [72], and the resolution in the time and frequency domains is linked to the type of base function used for transformation. The resolution expands (or contracts) according to a scale factor and is temporally shifted along the entire definition range of the signal.…”
Section: Comparation On the Performances Of Different Denoising Methodsmentioning
confidence: 99%
“…The discrete wavelet transform (DWT), which provides a window changing with the frequency to analyze and process the time-frequency signal, can decompose a signal into many scales which ranges from the roughest scale to the finest one [16]. With its outstanding feature of detecting singularities and transients [17], DWT has been widely used in spectra data to realize noise reduction. The process of baseline correcting is as follows: With the ability of loading spectra data, saving, baseline correction, and de-noising, peak detection module can automatically search peak and be matched with NIST database.…”
Section: Peak Detectionmentioning
confidence: 99%